Pemanfaatan Teknologi Informasi dalam Pelayanan Publik Kantor Manunggal Satu Atap Provinsi Maluku - Irna Ekram; Wahab Tuanaya; Marno Wance (Journal of Governance and Social Policy, 2022)
Weak mastery of information technology for single-roof office employees in Maluku Province can hinder the service of a Driving License (SIM). There are several indications of research problems such as ineffective communication and slow service of office employees in operating technology, causing ineffective and inefficient work, especially with regard to vehicle archive management, vehicle physical checks, as well as in terms of vehicle data verification services on the results of physical checks carried out. The purpose of the study was to determine the use of technology in performing public services at the Manunggal One Roof office. The research method used is descriptive qualitative by conducting direct interviews with the main informants who have been determined. The research novelties are (1). Integrated administrative system services by using certain applications online to the public to obtain information and knowledge. (2). Utilization of information technology that is more effective and efficient still requires online-based training for employees of the one-stop office of Maluku Province. (3). It is necessary to recruit employees who have good technological mastery skills so that they can perform services effectively and efficiently.